2013
DOI: 10.5468/ogs.2013.56.5.289
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic malignancy in pregnancy

Abstract: Gynecologic malignancy during pregnancy is a stressful problem. For the diagnosis and treatment of malignancy during pregnancy, a multidisciplinary approach is needed. Patients should be advised about the benefits and risk of treatment. When selecting a treatment for malignancy during pregnancy, the physiologic changes that occur with the pregnancy should be considered. Various diagnostic procedures that do not harm the fetus can be used. Laparoscopic surgery or laparotomy may be safely performed. The staging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…In our study, we found that gynecological malignancies accounted for approximately 80% of all malignant diseases with pregnancy during 2008. The most common pregnancy associated malignancies worldwide are cervical cancer, breast cancer, lymphoma, ovarian cancer, and melanoma [ 12 , 14 , 15 ]. Of these, cervical and breast cancers account for 50% of all cancers occurring during pregnancy [ 15 ], which is a lower rate than is seen in the present study (78%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that gynecological malignancies accounted for approximately 80% of all malignant diseases with pregnancy during 2008. The most common pregnancy associated malignancies worldwide are cervical cancer, breast cancer, lymphoma, ovarian cancer, and melanoma [ 12 , 14 , 15 ]. Of these, cervical and breast cancers account for 50% of all cancers occurring during pregnancy [ 15 ], which is a lower rate than is seen in the present study (78%).…”
Section: Discussionmentioning
confidence: 99%
“…The most common pregnancy associated malignancies worldwide are cervical cancer, breast cancer, lymphoma, ovarian cancer, and melanoma [ 12 , 14 , 15 ]. Of these, cervical and breast cancers account for 50% of all cancers occurring during pregnancy [ 15 ], which is a lower rate than is seen in the present study (78%). The obstetrician will often have the best opportunity to make the diagnosis of malignancy during pregnancy, so awareness of the associated symptoms is required during regular pre-natal checkups.…”
Section: Discussionmentioning
confidence: 99%
“…Once the termination of a pregnancy is adopted, it is possible either on the request of the patient to the end of the first trimester or on the basis of oncological indication to the end of the 24th week of pregnancy [42]. The treatment algorithm of pregnancy-associated breast cancer is summarized in Fig.…”
Section: Treatment Management Of Pabc Patientsmentioning
confidence: 99%
“…Reconstruction operations should be postponed until the period after birth, with respect to pregnancy-related changes in the other breast and the subsequent undesired cosmetic effects [42]. In early BC with clinically negative lymph nodes in the axilla, standard treatment is currently sentinel lymph node biopsy (SLNB).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Treatment used in patients with cervical cancer diagnosed in the second trimester of pregnancy depends on tumour stage. Cervical cancer diagnosed in the third trimester is an indication for Caesarean section due to foetal maturity, followed by standard therapy [ 42 ].…”
Section: Treatment Of Tumours Occurring During Pregnancymentioning
confidence: 99%